Pacific profiles ADB projects in the Pacific - Salamon, Robert; Del Rosario, Raul Bu.; Asian Development Bank. Information Office (Manila Asian Development Bank, 1995)
Examines how the Asian Development Bank supports development in Pacific Island nations through loans and technical assistance. Focuses on six ADB-financed projects in the Cook Islands, Fiji, and Western Samoa.
"D96574"--Cassette label
Narrator, Robert H. Salamon
Keywords: Asian Development Bank; Economic assistance -- Islands of the Pacific; Technical assistance -- Islands of the Pacific; Documentary films